Sexual blackmail: a modern history - McLaren, Angus (Harvard University Press, 2002)
Machine generated contents note: INTRODUCTION 1 --1 SODOMY AND THE INVENTION OF BLACKMAIL 10 --2 THE MODERN MANIA FOR MORALITY 30 --3 WOMANIZING ACROSS CLASS LINES 63 --4 ENTRAPPING THE JAZZ-AGE AMERICAN MALE 81 --5 THE HOMOSEXUAL TARGET BETWEEN THE WARS 105 --6 EXPLOITING RACIAL ANXIETIES 144 --7 BLACKMAIL AND THE NEW WOMAN 164 --8 CAUTIONARY TALES OF ADULTERY AND ABORTION 192 --9 DISARMING THE POSTWAR BLACKMAILER 220 --10 THE GAY MOVEMENT'S ATTACK ON VICTIMIZATION 239 --11 FROM BLACKMAIL TO TABLOID EXPOSE 256 --CONCLUSION 277